Lipid mobilizaton and acyl-coenzyme a dehydrogenase abundance in the postpharyngeal gland of a leaf-cutng ant - Vieira, A. S. [UNESP]; Bueno, O. C. [UNESP] (Universidade Estadual de Feira de Santana, 2016)
The postpharyngeal gland (PPG) in ants has a central role in lipid accumulaton. Our objectve was to investgate whether the PPG of workers of the leaf-cutng ant Ata sexdens rubropilosa (F.) performs lipid mobilizaton to the hemolymph, and to verify whether lipids in gland cells are in part oxidized to acetyl-CoA. Increased levels of faty acids were observed in both the PPG and the hemolymph after 48 h of lipid supplementaton. In contrast, after 120 h of lipid supplementaton, faty acid levels were reduced in the PPG and significantly increased in the hemolymph. The gland cells of the PPG of workers supplemented with lipids exhibited a high amount of Acyl-CoA dehydrogenase, and the lipids were in part β-oxidized to Acetyl-CoA. These fiundings suggest that the PPG of A. sexdens rubropilosa workers mobilize faty acids from their gland cells to the hemolymph. Further work will be needed to elucidate lipid transport from the hemolymph to other organs in this organism.
Keywords: Atni; Confocal microscopy; GC-MS; Hemolymph; Insects